2004
DOI: 10.1371/journal.pbio.0020296
|View full text |Cite
|
Sign up to set email alerts
|

Sir2-Independent Life Span Extension by Calorie Restriction in Yeast

Abstract: Calorie restriction slows aging and increases life span in many organisms. In yeast, a mechanistic explanation has been proposed whereby calorie restriction slows aging by activating Sir2. Here we report the identification of a Sir2-independent pathway responsible for a majority of the longevity benefit associated with calorie restriction. Deletion of FOB1 and overexpression of SIR2 have been previously found to increase life span by reducing the levels of toxic rDNA circles in aged mother cells. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
392
3
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(423 citation statements)
references
References 38 publications
24
392
3
2
Order By: Relevance
“…Another CR pathway induced by 0.05% glucose (Kaeberlein et al 2004(Kaeberlein et al , 2005bEaslon et al 2007) has recently been characterized. Interestingly, this severe CR condition does not require respiration or the Sir2 family to extend life span.…”
Section: Requirement Of Respiration and The Sir2 Family In Aat1 Mdh1mentioning
confidence: 99%
See 1 more Smart Citation
“…Another CR pathway induced by 0.05% glucose (Kaeberlein et al 2004(Kaeberlein et al , 2005bEaslon et al 2007) has recently been characterized. Interestingly, this severe CR condition does not require respiration or the Sir2 family to extend life span.…”
Section: Requirement Of Respiration and The Sir2 Family In Aat1 Mdh1mentioning
confidence: 99%
“…Variations in CR protocols have also been described in which limitation of amino acids and/or further reduction in carbon source are employed (Jiang et al 2000(Jiang et al , 2002. Many studies have shown that the Sir2 family plays an important role under moderate CR conditions (0.5% glucose) (Lin et al 2000(Lin et al , 2002Wood et al 2004;Lamming et al 2005;Easlon et al 2007); however, Sir2 appeared to be dispensable under more severe CR conditions (Jiang et al 2000(Jiang et al , 2002Kaeberlein et al 2004;Lamming et al 2005;Easlon et al 2007). Although these CR regimens may represent other longevity pathways that function in parallel to moderate CR in rich media, it remains highly possible that moderate CR also induces other proteins in addition to the Sir2 family to extend life span .…”
mentioning
confidence: 99%
“…Reports suggest that they might mediate the action of dietary caloric restriction on lifespan extension (Tissenbaum and Guarente, 2001;Libina et al, 2003;Lamming et al, 2005), although conflictions reports exist (Kaeberlein et al, 2004(Kaeberlein et al, , 2005. Research in yeast found that Sir2 and its homolog, Hst2, mediate the lifespan extension effect of caloric restriction in a complementary fashion (Lamming et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since NADH has been described as a Sir2p inhibitor, calorie restriction results in higher Sir2p activity Lin & Guarente, 2003), contributing to life-span extension. Nevertheless, the importance of this ratio to the activation of Sir2p has been questioned (Anderson et al, 2003;Kaeberlein et al, 2004;Grubisha et al, 2005).Chronological ageing in yeast has been used as a valuable model to study oxidative damage and ageing of the postmitotic tissues of higher organisms MacLean et al, 2001). In post-diauxic cultures, respiration is the main source of energy for the yeast cell.…”
mentioning
confidence: 99%